Cross-Border Patenting, Globalization, and Development - Jesse LaBelle; Inmaculada Martinez-Zarzoso; Ana Maria Santacreu; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2023)
We build a stylized model that captures the relationships between cross-border patenting, globalization, and development. Our theory delivers a gravity equation for cross-border patents. To test the model's predictions, we compile a new dataset that tracks patents within and between countries and industries, for 1980-2019. The econometric analysis reveals a strong, positive impact of policy and globalization on cross-border patent flows, especially from North to South. A counterfactual welfare analysis suggests that the increase in patent flows from North to South has benefited both regions, with South gaining more than North post-2000, thus lowering real income inequality in the world.
Keywords: F63; O14; O33; O34; 330; cross-border patents; gravity; policy; globalization; development